1998
DOI: 10.1159/000006763
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fish Oils Appears to Reduce Infarct Size as Estimated from Peak Creatine Kinase and Lactate Dehydrogenase Activities

Abstract: In 753 patients with acute myocardial infarction, use of fish oils (FO, n = 242) before onset of infarction seemed to reduce infarct size as estimated from peak creatine kinase (CKmax) and lactate dehydrogenase (LDmax) activities. The study had an observational exposed/nonexposed design, and both crude and adjusted effects were looked for. Crude Effects: In the restricted cohort of patients not receiving thrombolytic treatment (n = 411), FO reduced CKmax from 879 to 759 U/l (2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Further evidence for a protective effect of omega-3 fatty acids comes from two recent studies by Landmark et al 24,25 who reported that chronic intake of fish or fish oil was associated with a reduction in infarct size as estimated by the frequency of Q-wave infarcts and by peak creatine kinase and lactate dehydrogenase activities after MI. In contrast to all the studies demonstrating a beneficial association, the AlphaTocopherol, Beta-Carotene Cancer Prevention Study found that estimated omega-3 fatty acid intake from fish was associated with a trend toward increased relative risk of coronary death after adjustment for trans, saturated, and cis-monounsaturated fatty acids.…”
Section: Epidemiological and Observational Studies Coronary Heart Dismentioning
confidence: 99%
“…Further evidence for a protective effect of omega-3 fatty acids comes from two recent studies by Landmark et al 24,25 who reported that chronic intake of fish or fish oil was associated with a reduction in infarct size as estimated by the frequency of Q-wave infarcts and by peak creatine kinase and lactate dehydrogenase activities after MI. In contrast to all the studies demonstrating a beneficial association, the AlphaTocopherol, Beta-Carotene Cancer Prevention Study found that estimated omega-3 fatty acid intake from fish was associated with a trend toward increased relative risk of coronary death after adjustment for trans, saturated, and cis-monounsaturated fatty acids.…”
Section: Epidemiological and Observational Studies Coronary Heart Dismentioning
confidence: 99%
“…In the US Physicians Health Study (21,000 males), the subjects consuming fish once or more per week had a 52% lower sudden death rate compared with subjects not consuming fish; the incidence of MI and non-sudden cardiac death was similar in the two groups [114]. In any case, the subjects consuming n-3 fatty acids at the moment of a MI presented lower scar extension and higher incidence of non-Q MI [115,116].…”
Section: Effects On Cardiac and Arrhythmic Death Epidemiologymentioning
confidence: 91%
“…In any case, the analysis of several epidemiological observations and secondary prevention trials showed an association between n-3 fatty acid uptake and reduction of sudden death more than the reduction of non-fatal cardiovascular events [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130].…”
Section: Effects On Cardiac and Arrhythmic Death Epidemiologymentioning
confidence: 99%
“…In one prospective cohort study of 745 post-acute MI patients in Norway, peak serum creatine kinase levels (used as a surrogate for Q-wave infarction) correlated negatively with fish consumption [54].…”
Section: Randomized Controlled Trial Evidence In Cardiovascular Diseasementioning
confidence: 99%